The relative? application of the rule of law in International Criminal Law (2017)
It is assumed in this text that criminal law must adapt to the limits that derive from the Rule of Law. That is why the Rome Statute provision is imposed in which a range of sources that are notoriously strange to the Criminal Law are foreseen. Thus, desp